PENGARUH PEMBANGUNAN INFRASTRUKTUR JALAN RAYA TERHADAP PERTUMBUHAN EKONOMI KABUPATEN SUMBAWA - K Kamaruddin; Wahyu Haryadi; Mulvy Wahyudi (Jurnal Ekonomi & Bisnis, 2021)
The purpose of this study was to know the effect of road infrastructure development toward economic growth in Sumbawa District. The type of this study was associative with quantitative methods. The technique used to collect data in this study were through observation, interviews and documentation with data analysis using simple linear regression with SPSS 16.00 version. Based on result of data analysis showed that the X variable had significant effect toward the Y variable, it was based on the value of t-value was of 6.318 and t-table was of 2.776 stated that for every 1% addition to the infrastructure value, the economic value was increases of 0.046, that regression coefficient was positive, so it can be said that the direction of the effect of the variable X toward Y was positive. Based on the t-value, it was known that t-value was of 6,318< t-table of 2.776 with a significant degree of 5% so that it can be concluded that the X variable did not have effect toward the Y variable. In other words Ha was accepted which means there was effect of the X variable toward the Y variable.